Lactobacilli and Bifidobacteria: A Parapostbiotic Approach to Study and Explain Their Mutual Bioactive Influence - Clelia Altieri; Alfonso Filippone; Antonio Bevilacqua; Maria Rosaria Corbo; Milena Sinigaglia (Foods)
Three strains of Lactiplantibacillus plantarum and three bifidobacteria (Bifidobacterium animalis subsp. lactis, Bifidobacterium breve, and Bifidobacterium subtile) were used as target strains; in addition, for each microorganism, the cell-free supernatant (CFS) was produced and used as an ingredient of the growth medium. Namely CFSs from lactobacilli were used on bifidobacteria and CFSs from bifidobacteria were used on lactobacilli. The viable count was assessed, and the data were modelled through a reparametrized Gompertz equation cast both in the positive and negative form to evaluate the parameters t-7log, which is the time after which the viable count was 7 log CFU/mL, and the t-7log*, which is the time after which the viable count was below 7 log CFU/mL; the difference between the t-7log* and t-7log defines the stability time. Statistics through a multiparametric ANOVA (analysis of variance) provided evidence for the presence of a bifidogenic and/or bioactive factor produced by bifidobacteria and active on lactobacilli, and vice versa (bioactive factor of lactobacilli with a functional effect on bifidobacteria), although further studies are required to better explain the mechanisms beyond the positive effects. In addition, the influence on the target strains can be found during the growth phase (stimulation), as well as during senescence and death phase (protective effect), with a strong strain/species dependence on both CFS production and target strain.